Get training or wait? Long-run employment effects of training programs for the unemployed in West Germany - Bernd Fitzenberger; Aderonke Osikominu; Robert Völter (Institute for the Study of Labor (IZA), 2006)
Long-term public sector sponsored training programs often show little or negative short-run employment effects and often it is not possible to assess whether positive long-run effects exist. Based on unique administrative data, this paper estimates the long-run differential employment effects of three different types of training programs in West Germany. We use inflows into unemployment for the years 1986/87 and 1993/94 and apply local linear matching based on the estimated propensity score to estimate the effects of training programs starting during 1 to 2, 3 to 4, and 5 to 8 quarters of unemployment. The results show a negative lock-in effect for the period right after the beginning of the program and significantly positive treatment effects on employment rates in the medium- and long-run. The differential effects of the three programs compared to one another are mainly driven by differences in the length of the lock-in periods.
Keywords: C14; J68; H43; 330; multiple treatments; training programs; employment effects; local linear matching; administrative data; active labor market programs; Arbeitsmarktpolitik; Weiterbildung; Wirkungsanalyse; Arbeitslosigkeit; Schätzung; Deutschland